Cereblon versus VHL: Hijacking E3 ligases against each other using PROTACs - Girardini, Miriam (Bioorg Med Chem, 2019)
The von Hippel-Lindau (VHL) and cereblon (CRBN) proteins are substrate recognition subunits of two ubiquitously expressed and biologically important Cullin RING E3 ubiquitin ligase complexes. VHL and CRBN are also the two most popular E3 ligases being recruited by bifunctional Proteolysis-targeting chimeras (PROTACs) to induce ubiquitination and subsequent proteasomal degradation of a target protein. Using homo-PROTACs, VHL and CRBN have been independently dimerized to induce their own degradation. Here we report the design, synthesis and cellular activity of VHL-CRBN hetero-dimerizing PROTACs featuring diverse conjugation patterns. We found that the most active compound 14a induced potent, rapid and profound preferential degradation of CRBN over VHL in cancer cell lines. At lower concentrations, weaker degradation of VHL was instead observed. This work demonstrates proof of concept of designing PROTACs to hijack different E3 ligases against each other, and highlights a powerful and generalizable proximity-induced strategy to achieve E3 ligase knockdown.